Pengembangan Modul Elektronik Berbantuan Aplikasi Canva sebagai Bahan Ajar Materi Cerpen Sekolah Menengah Atas - Afifah, Sakhia; AR, Hasnah Faizah; Permatasari, Silvia (PAKAR Pendidikan, 2024)
This research is development research titled "Development of Electronic Modules Assisted by Canva Application as Teaching Materials for Short Story Materials in Senior High School". This research is motivated by students' language skills, especially their ability to write short stories, which are still considered lacking. With that, the formulation of the problems studied is 1) how is the procedure for developing electronic modules, 2) how is the quality of electronic modules, 3) how is the level of effectiveness of using electronic modules, and 4) how is the level of practicality of using electronic modules in the learning process. This study aims to determine the module development procedure, quality, effectiveness, and practicality of the electronic module made. The development model used is ADDIE, which includes the stages of analysis, design, development, trial, and assessment. The test subject is the XI grade students of YLPI Pekanbaru High School, as many as 25 students. This study's data and data sources were obtained from teacher interviews, student needs questionnaires, expert validation, pretest-posttest, and assessments from teachers and students. The quality of the electronic module is seen from expert validation, which has very good results and can be used as teaching material. The effectiveness of the electronic module is evidenced by the significant difference between the pretest and post-test results obtained by students before and after using the product. The practicality of the electronic module is shown by the way teachers and students assess it and the results of practical use as teaching materials for short stories. Thus, the electronic module assisted by the Canva application is declared to be used as teaching material for short stories.